THE ROLE OF DIGITAL LEARNING MEDIA IN DISTANCE LEARNING DURING THE PANDEMIC - Lina Septianasari; Anne Nurlatifah (JELLi Journal, 2021)
Digital learning media become the most important tools in distance learning since they can bridge the interaction between the teachers and the students due to their distance. The aim of this paper is to determine the role of digital learning media in distance learning. This study used a descriptive qualitative method to dig the finding by using observation and interview as the instruments. The results showed that teachers’ creativity was needed in operating the learning media during the teaching and learning process to manage their fun English classes. Nonetheless, Teachers also need to be more selective in using the learning media to deliver the material and to assess students’ learning outcomes.